Analyzing OpenStreetMap Road Data and Characterizing the Behavior of Contributors in Ankara, Turkey - Hacar, Muslum; Kilic, Batuhan; Sahbaz, Kadir (MDPI, 2018)
The usage of OpenStreetMap (OSM), one of the resources offered by Volunteered Geographic Information (VGI), has rapidly increased since it was first established in 2004. In line with this increased usage, a number of studies have been conducted to analyze the accuracy and quality of OSM data, but many of them have constraints on evaluating the profiles of contributors. In this paper, OSM road data have been analyzed with the aim of characterizing the behavior of OSM contributors. The study area, Ankara, the capital city of Turkey, was evaluated with several network analysis methods, such as completeness, degree of centrality, betweenness, closeness, PageRank, and a proposed method measuring the activation of contributors in a bounded area from 2007-2017. An evaluation of the results was also discussed in this paper by taking into account the following indicators for each year: number of nodes, ways, contributors, mean lengths, and sinuosity values of roads. The results show that the experience levels of the contributors determine the contribution type. Essentially, more experience makes for more detailed contributions.
Keywords: OSM; activation density; network analysis; centrality; VGI; QUALITY ASSESSMENT; STREET NETWORKS; URBAN STREETS; INFORMATION; PATTERNS; Computer Science; Physical Geography; Remote Sensing